Proceedings of the 14th European Conference on Artificial Life ECAL 2017 2017
DOI: 10.7551/ecal_a_050
|View full text |Cite
|
Sign up to set email alerts
|

Lexicase selection outperforms previous strategies for incremental evolution of virtual creature controllers

Abstract: Evolving robust behaviors for robots has proven to be a challenging problem. Determining how to optimize behavior for a specific instance, while also realizing behaviors that generalize to variations on the problem often requires highly customized algorithms and problem-specific tuning of the evolutionary platform. Algorithms that can realize robust, generalized behavior without this customization are therefore highly desirable. In this paper, we examine the Lexicase selection algorithm as a possible general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…Among the most significant of these variations is epsilon lexicase selection, in which "exactly the lowest error" in the description of the algorithm is replaced with "within epsilon of the lowest error" for a suitably defined epsilon; this has proven to be particularly effective on problems with floating-point errors [16,17]. Additionally, lexicase selection has been effectively used to solve problems in areas such as boolean logic and finite algebras [11,13,18], evolutionary robotics [22], and boolean constraint satisfaction using genetic algorithms [21].…”
Section: Background On Lexicase Selectionmentioning
confidence: 99%
“…Among the most significant of these variations is epsilon lexicase selection, in which "exactly the lowest error" in the description of the algorithm is replaced with "within epsilon of the lowest error" for a suitably defined epsilon; this has proven to be particularly effective on problems with floating-point errors [16,17]. Additionally, lexicase selection has been effectively used to solve problems in areas such as boolean logic and finite algebras [11,13,18], evolutionary robotics [22], and boolean constraint satisfaction using genetic algorithms [21].…”
Section: Background On Lexicase Selectionmentioning
confidence: 99%
“…The animat, simulation environment, and wall-crossing task are continuations of previous work originally reported with respect to Lexicase selection in Moore and Stanton (2017). Specific design parameters are detailed in that work and its references.…”
Section: Methodsmentioning
confidence: 99%
“…If multiple individuals remain after all objectives have been used, a random selection is applied to the remaining individuals and recorded as a tiebreak event. For a full description of the Lexicase selection algorithm employed in this paper refer to Moore and Stanton (2017).…”
Section: Torso Dimensionmentioning
confidence: 99%
“…Previous studies have shown lexicase selection outperforming tournament selection and other parent selection methods in areas such as automatic program synthesis [3,13], boolean logic and finite algebras [12,14,25], evolutionary robotics [28], and boolean constraint satisfaction using genetic algorithms [27]. Additionally, ϵ-lexicase, a relaxed version of lexicase selection that at each step keeps any individuals within some threshold of the best individual, has performed well on symbolic regression problems [17,19].…”
Section: Lexicase Selectionmentioning
confidence: 99%